2009
DOI: 10.1590/s1516-89132009000700029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of αRYR hotspot region 1 from broiler chicken

Abstract: Samples of Pectoralis major m. were collected, and an RT-PCR analysis of the a-Ryanodine receptor (a RYR) from chicken mRNA hotspot region spanning aminoacid residues 386 to 540, numbered according to the turkey sequence, revealed two classes of transcripts. The sequences of the first class were similar to turkey and human with 97% and 74% of identity, respectively, and included all transcripts with substitutions in the nucleotide sequence. The second class was characterized by the deletion of nucleotides, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The fragments produced from the amplification of the cDNA specific hotspot followed by the electrophoresis gel showed no difference in size between the different treatments. The fragments were exactly the same size (approximately 600 bp) as those reported by Ziober et al (2009). In contrast to these results, Chiang et al (2004) reported three transcripts of different sizes that corresponded to three variants of RyR in turkeys.…”
Section: Resultssupporting
confidence: 46%
See 1 more Smart Citation
“…The fragments produced from the amplification of the cDNA specific hotspot followed by the electrophoresis gel showed no difference in size between the different treatments. The fragments were exactly the same size (approximately 600 bp) as those reported by Ziober et al (2009). In contrast to these results, Chiang et al (2004) reported three transcripts of different sizes that corresponded to three variants of RyR in turkeys.…”
Section: Resultssupporting
confidence: 46%
“…As shown by Marchi I.L. Ziober et al et al (2009) halothane treatment itself plays a role as a stressor and therefore may also be a modulating agent for gene expression, as occurred with heat stress. The presence of truncated proteins originated from the deletions of different nucleotides, altered the frame shift, creating a premature stop codon that was the highest in those birds exposed to halothane ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The chicken αRYR protein and cDNA sequences can be accessed from GenBank (accessions X95266, XM_424193, XM_428139, XM_427376). Ziober et al (2009) reported the sequence of the cDNA encoding the chicken region hotspot 1 αRYR (corresponding to amino acids 386-540 relative to the turkey sequence) and analyzed the N-terminal portion of αRYR. This analysis showed that the chicken transcripts share 97 and 74% sequence identity with the turkey αRYR and mammalian RYR1 sequences, respectively (Figure 4).…”
Section: Molecular Biology and Poultry Ryr Mutationmentioning
confidence: 99%
“…This analysis showed that the chicken transcripts share 97 and 74% sequence identity with the turkey αRYR and mammalian RYR1 sequences, respectively (Figure 4). Note that the sequences of the chicken αRYR transcripts described by Ziober et al (2009) show no similarity to the Gallus gallus genomic sequences in the GenBank database. The reason for this discrepancy may be that the region of the αRYR transcript sequenced by Ziober et al (2009) was similar to a region on chromosome 3 from G. gallus that contains a gap, representing a DNA fragment with a series of undetermined nucleotides.…”
Section: Molecular Biology and Poultry Ryr Mutationmentioning
confidence: 99%
“…Therefore, the effects of a defective RYR protein are not yet as well understood in birds as they are in the pig, and how these mutations in RyR lead to PSE meat in poultry is not known Chiang, 2003, 2009). Ziober et al (2009Ziober et al ( , 2010 concluded that the expression pattern of α-RyR transcripts in broiler chickens is altered by heat stress and halothane treatment, irrespective of PSE occurrence. Although the sequence of the chicken genome is nearly complete (http://www.ensembl.org/Gallus_gallus/Info/Index), the genomic and transcript sequences of chicken α-RyR have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%